2018
DOI: 10.1016/j.gaceta.2017.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to nutritional recommendations in vending machines at secondary schools in Madrid (Spain), 2014-2015

Abstract: Almost all the products on display in secondary school vending machines in Madrid were in breach of the Consensus Document on School Food, mainly due to an excess of calories, sugars and fats. Compulsory nutritional criteria and a procedure for monitoring adherence should be established, specifying those responsible for performing this task and the corrective measures to be applied in the event of non-compliance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
4
0
1
Order By: Relevance
“…Yet, the Spanish Strategy for Nutrition, Physical Activity, and the Prevention of Obesity (NAOS strategy) appeals to parents’ responsibility and voluntary self-regulation of the food industry [28]. In addition, previous research has shown that, in regard to the nutritional quality of the products sold in vending machines within schools, compliance with NAOS recommendations is low [29].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, the Spanish Strategy for Nutrition, Physical Activity, and the Prevention of Obesity (NAOS strategy) appeals to parents’ responsibility and voluntary self-regulation of the food industry [28]. In addition, previous research has shown that, in regard to the nutritional quality of the products sold in vending machines within schools, compliance with NAOS recommendations is low [29].…”
Section: Introductionmentioning
confidence: 99%
“…In Spain, the assortment of vending machines included only 10.5% recommended products (water, milk, and dairy products) and 80.5% food and drinks with high energy, fat, or sugar content and low vitamin and mineral content [ 45 , 46 ]. The availability of unhealthy drinks and foods in school vending machines contributes to unfavorable eating behaviors among teenagers [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Poco saludable Saludable N°% N°% N°% están disponibles en los establecimientos y más del 80% de sus productos no son saludables [28][29][30][31][32] . En este orden de ideas, es un punto importante a intervenir en los entornos alimentarios educativos 24 .…”
Section: No Saludableunclassified